2013
DOI: 10.1162/jocn_a_00327
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 Receptor Modulation of Human Response Inhibition and Error Awareness

Abstract: Response inhibition, comprising action cancellation and action restraint, and error awareness are executive functions of considerable clinical relevance to neuropsychiatric disorders. Nevertheless, our understanding of their underlying catecholamine mechanisms, particularly regarding dopamine, is limited. Here, we used the dopamine D2 agonist cabergoline to study its ability to improve inhibitory control and modulate awareness of performance errors. A randomized, double-blind, placebo-controlled, crossover des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 54 publications
1
40
0
Order By: Relevance
“…Low doses of D2 agonists reduce dopamine signalling by targeting pre-synaptic autoreceptors, diminishing phasic dopamine bursts and consequently decreasing reward learning and increasing relative learning from punishment [30][31][32][33] . Other studies have shown that low doses of cabergoline increase error awareness and response inhibition 51 , and cause a shift to a more conservative risk taking strategy 52 , all possibly due to a relative shift in indirect over direct pathway functioning. In the absence of nearly any other behavioural or EEG alteration, cabergoline caused a strong behavioural bias for C4B.…”
Section: Discussionmentioning
confidence: 98%
“…Low doses of D2 agonists reduce dopamine signalling by targeting pre-synaptic autoreceptors, diminishing phasic dopamine bursts and consequently decreasing reward learning and increasing relative learning from punishment [30][31][32][33] . Other studies have shown that low doses of cabergoline increase error awareness and response inhibition 51 , and cause a shift to a more conservative risk taking strategy 52 , all possibly due to a relative shift in indirect over direct pathway functioning. In the absence of nearly any other behavioural or EEG alteration, cabergoline caused a strong behavioural bias for C4B.…”
Section: Discussionmentioning
confidence: 98%
“…How might this be explained? First, animal studies and human imaging work show that higher D2 -like receptor availability in the dorsal striatum is associated with faster SSRTs (Eagle and Robbins 2003, Ghahremani, Lee et al 2012) and administration of agonists that target these receptors also speed SSRT (Nandam, Hester et al 2013). In contrast, D2-like receptor antagonism slows SSRT, and self-reported impulsivity has been linked to slower SSRTs and reduced midbrain D2-like receptor availability (Lee, London et al 2009)(Logan, Schachar et al 1997, Buckholtz, Treadway et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between D2/D3 receptor expression and impulsivity was recently reported in humans using PET while participants performed the SST such that D2/D3 availability was negatively correlated with speed of response inhibition and positively correlated with inhibition-related fMRI activation in frontostriatal circuitry [73]. Moreover, administration of the D2-like agonist cabergoline in human healthy controls resulted in an increase in stop signal reaction time (decreased response impulsivity) in the SST [74]. Administration of the D2/D3 receptor antagonist nafadotride into the accumbens shell in rats enhanced premature responding in high impulsive rats [75], and rats that have lower D2/D3 receptor availability in the ventral striatum display greater response impulsivity on the 5CSRTT [76].…”
Section: Underlying Neurocircuitry Of Impulsivitiesmentioning
confidence: 96%